Congenital pyloric atresia and epidermolysis bullosa: Report of a rare association - Pradyumna Pan (Wolters Kluwer Medknow Publications, 2021)
Pyloric atresia (PA) is an unusual congenital disorder that accounts for about 1% of all intestinal atresia, with an incidence around 1 in 100,000 live births. PA may occur as an isolated disorder or may be associated with epidermolysis bullosa (EB). EB comprises a heterogeneous group of cutaneous genetic diseases of inherited blistering and skin fragility disorders. Wound management in EB is complex and influenced by several comorbidities and the fragility of the skin. The prognosis of children with EB depends on the type of mutation inherited. Some types are mild and even improve with age, while others are so severe it is not likely that a child to survive into adulthood. We present three cases of PA in this article and one in conjunction with junctional EB.